Converging roles of ion channels, calcium, metabolic stress, and activity pattern of Substantia nigra dopaminergic neurons in health and Parkinson's disease. (23rd March 2016) - Duda, Johanna; Pötschke, Christina; Liss, Birgit
Abstract: Dopamine‐releasing neurons within the Substantia nigra (SN DA) are particularly vulnerable to degeneration compared to other dopaminergic neurons. The age‐dependent, progressive loss of these neurons is a pathological hallmark of Parkinson's disease (PD), as the resulting loss of striatal dopamine causes its major movement‐related symptoms. SN DA neurons release dopamine from their axonal terminals within the dorsal striatum, and also from their cell bodies and dendrites within the midbrain in a calcium‐ and activity‐dependent manner. Their intrinsically generated and metabolically challenging activity is created and modulated by the orchestrated function of different ion channels and dopamine D2‐autoreceptors. Here, we review increasing evidence that the mechanisms that control activity patterns and calcium homeostasis of SN DA neurons are not only crucial for their dopamine release within a physiological range but also modulate their mitochondrial and lysosomal activity, their metabolic stress levels, and their vulnerability to degeneration in PD. Indeed, impaired calcium homeostasis, lysosomal and mitochondrial dysfunction, and metabolic stress in SN DA neurons represent central converging trigger factors for idiopathic and familial PD. We summarize double‐edged roles of ion channels, activity patterns, calcium homeostasis, and related feedback/feed‐forward signaling mechanisms in SN DA neurons for maintaining and modulating their physiological function, but also for contributing to their vulnerability in PD‐paradigms. We focus on the emerging roles of maintained neuronal activity and calcium homeostasis within a physiological bandwidth, and its modulation by PD‐triggers, as well as on bidirectional functions of voltage‐gated L‐type calcium channels and metabolically gated ATP‐sensitive potassium (K‐ATP) channels, and their probable interplay in health and PD. We propose that SN DA neurons possess several feedback and feed‐forward mechanisms to protect and adapt their activity‐pattern and calcium‐homeostasis within a physiological bandwidth, and that PD‐trigger factors can narrow this bandwidth. We summarize roles of ion channels in this view, and findings documenting that both, reduced as well as elevated activity and associated calcium‐levels can trigger SN DA degeneration. This article is part of a special issue on Parkinson disease . Abstract : We propose that SN DA neurons possess several feedback and feed‐forward mechanisms to protect and adapt their activity‐pattern and calcium‐homeostasis within a physiological bandwidth, and that PD‐trigger factors can narrow this bandwidth. We summarize roles of ion channels in this view, and findings documenting that both, reduced as well as elevated activity and associated calcium‐levels can trigger SN DA degeneration. This article is part of a special issue on Parkinson disease .